Análise comparativa das emissões de gases de efeito estufa para dois sistemas de climatização em um edifício universitário no Rio Grande do Norte - Garcia, Lígia da Costa (2021)
This work develops a Life Cycle Assessment (LCA) for the air-conditioning system currently installed at the School of Science and Technology of the Federal University of Rio Grande do Norte. An alternative system is designed, based on absorption refrigeration with solar collectors. The emissions of greenhouse gases are quantified for both systems and compared. The study objects are a conventional air conditioning system (vapor compression) and another system, proposed and modeled, based on absorption refrigeration with solar input. In a cradle-to-grave approach, the projects have a power of 1735 kW. The equipment and materials used for installation, maintenance, transport, and disposal were accounted for. The electric energy required for the operation of both systems was also counted. As a result of the LCA, 355,712 kg CO2-eq/year was obtained for the vapor compression air conditioning system and 131,266 kg CO2-eq/year for the absorption air conditioning system with solar support. Hence, there were approximately 63 % less total emissions from the system by suggested absorption. The most significant difference was in relation to the stage of the operation, which confirms the need to use energies that generate less emissions, such as those coming from solar panels or collectors. Consideration of performance degradation of the air-conditioning systems increased variable emissions by 6 % for the conventional system, and by 3.8 % for the absorption solar system.